Assessment of Two Techniques for Remediation of Lacustrine Rocky Reef Spawning Habitat. (16th February 2021) - Gatch, Alexander J.; Koenigbauer, Scott T.; Roseman, Edward F.; Höök, Tomas O.
Abstract: Rocky reef habitats in lacustrine systems constitute important areas for lithophilic‐spawning fishes. Interstitial spaces created by the structure of rocky reefs form microenvironments where incubating embryos and juvenile fish are potentially protected from predators and physical displacement. However, if interstitial spaces are filled or blocked by sediment or biofouling, the reef structure may lose these benefits. Common practices to restore reef habitat include augmentation of existing reef structures or construction of new reefs, though these practices can be costly. We explored an alternative approach for reef remediation. In 2018, we developed two benthic sled cleaning devices that used either propulsion or pressurized water jets and were towed behind a small vessel to clean reefs. We used the devices to clean two impaired natural rocky reefs in Saginaw Bay, Lake Huron. We indexed effectiveness of cleaning by measured changes in substrate relative hardness before and after cleaning. A biological response to reef cleaning was also measured by egg deposition of fall (Lake Whitefish Coregonus clupeaformis ) and spring (Walleye Sander vitreus ) lithophilic spawners. We found that our propulsion cleaning device was more effective in increasing substrate relative hardness than was the water jet device, although this was not consistent among all study locations. We also found that egg deposition on study plots was variable, but in general, egg deposition was highest on study plots that had the greatest increases in relative hardness post‐cleaning. The practicality of cleaning devices is likely related to the magnitude of site‐specific degradation. Our results indicate that the use of these or similar devices can potentially increase the quality of spawning habitat by displacing sediments that have deposited on reef structures.